Antioxidant and antiproliferative activities of n-hexane extract and its fractions from Blumea balsamifera L. leaves - Binawati Ginting; Ilham Maulana; Mustanir Yahya; Nurdin Saidi; Murniana Murniana; Kartini Hasballah; Maulidna Maulidna; Siti Rawati (Wolters Kluwer Medknow Publications, 2022)
Blumea balsamifera is a plant species that has been popularly used to treat a broad spectrum of diseases. In efforts of tackling the increasing threat of cancers, B. balsamifera has been studied for its anticancer potentials. Hence, through this research, we aimed to evaluate the antioxidant and antiproliferative activities of n-hexane extract from B. balsamifera L. leaves along with its fractionation products. After the n-hexane extract has been obtained, the sample was column chromatographed using gradient elution with n-hexane:ethyl acetate solvent. All the isolation protocols produced 1 n-hexane extract and 10 different fractions (fractions 1-10). Antioxidant and antiproliferative effects of the samples were assessed based on 2,2-diphenyl-1-picrylhydrazyl and brine shrimp lethality test assay, respectively. None of the samples have a strong antioxidant level because all samples yielded IC50 of more than 100 ppm - the best of them was fraction 8 with IC50 = 113.716 ppm. On contrary, most of the samples were observed to have a potent antiproliferative effect, especially fraction 8 with LC50 = 2.00 ppm. Taken altogether, fraction 8 from the n-hexane extract of B. balsamifera L. leaves is the most potential candidate for proliferative disease therapy, where further studies confirming the results are required.